A Budget Impact Analysis of the VENTANA PD-L1 SP142 Immunohistochemistry Assay Versus the Dako PD-L1 IHC 22C3 Assay in Patients With Advanced or Metastatic Triple-Negative Breast Cancer Treated With Atezolizumab in Combination With Nab-Paclitaxel - Scatena, Cristian; Ravasio, Roberto; Raimondo, Paola; Giuliano, Mario (Farmeconomia. Health Economics and Therapeutic Pathways, 2021)
OBJECTIVE: To estimate the budget impact determined by the adoption of two different diagnostic strategies, SP142 assay or 22C3 assay, in the identification (in terms of PD-L1 status) of patients with mTNBC eligible for treatment with atezolizumab in combination with nab-paclitaxel. METHODS: The budget impact analysis (BIA) was conducted using a budget impact model (BIM) considering the Italian National Health Service’s (iNHS) perspective. The analysis assessed only the direct medical cost (tissue biopsy, PD-L1 assay, specialist visit, pharmacological treatment with atezolizumab in combination with nab-paclitaxel) of patients with PD-L1 positive mTNBC, and management of the adverse events associated with the pharmacological treatment administered. The BIM also considered the clinical benefits (progression free survival, PFS) resulting from the drug therapy administered on the basis of the results of the post-hoc analysis of the IMpassion130 clinical trial. The BIA was conducted over a 1-year time horizon. The median cost per patient in the progression-free state was also calculated. The costs were calculated using the net ex-factory prices (cancer drugs) and regional or national tariffs (tissue biopsy, PD-L1 assay, specialist visit and adverse events management). A sensitivity analysis was conducted to evaluate the base case result. RESULTS: The SP142 assay diagnostic pathway would result in a reduction of the iNHS expenditure of approximately 5.6 million euros (-12%). Almost all of the reduction in iNHS expenditure would be determined by the lower number of patients treated (SP142: 689 patients vs 22C3: 786 patients) with immunotherapy (-€ 5,530,871). Compared with 22C3 assay, the SP142 assay shows a cost per PFS month reduction of € 736 (€ 7,010 vs € 7,746). CONCLUSIONS: The use of the SP142 assay proved to be cost-effective compared to the 22C3 assay; the SP142 assay can support the choice of the most appropriate cancer drug, maximizing the effectiveness and minimizing the waste of healthcare resources.